Spatial association of Aedes aegypti with dengue fever hotspots in an endemic region. Issue 11 (November 2022) - Sharif, Mohiuddin; Khan, Md. Abdullah Saeed; Hasan, Mohammad Jahid; Naher, Tanzin; Rudra, Sujan; Fardous, Jannatul; Gozal, David; Rahman, Md Khalilur; Amin, Mohammad Robed
Abstract: Background and objective: Dengue is a vector-borne viral disease usually transmitted by Aedes mosquitoes. Around the world, the relationship between local vector density and frequency of dengue cases is being explored and needs further evidence. This study aimed to analyze the potential spatial relationships between the dengue vector ( Aedes aegypti ) and dengue cases in the megacity of Bangladesh during the 2019 dengue outbreak. Methods: Vector density measures were used to estimate spatial associations with dengue case distribution. Location was determined for 364 dengue cases who were admitted to Dhaka Medical College Hospital over a period of 4 months. Data were collected using a semi-structured questionnaire, and prior consent was ensured before participation. The Moran global index, Getis-Ord Gi∗, ordinary least squares regression, geographically weighted regression and count data regression methods were used for spatial analysis. Results: We found that dengue case distribution was not associated with immature Aedes aegypti mosquito (larvae) density across the city. The relationship between larval density measured by the Breteau Index (BI) and House Index (HI) with dengue cases was nonstationary and not statistically significant. Conclusion: The location of dengue cases appears to be unrelated to vector distribution and vector density. These findings should prompt the search for other transmission risk factors.